Development of autonomous vehicle for road marks painting - Hashem, Mohammed Abdo (2017)
The painting marks on the road in the existing system includes two main tasks that are accomplished separately and in respectively during the road marking painting; firstly, the pre-marker is used to draw a field sketch in advance to avoid faulty marking. The road surface is pre-marked by a line using an auxiliary equipment pre-marker which determines the exact position of the road that will be painted later like in the middle, at the right or left sides of roads, etc. In the second task, the user will move the thermoplastic or cold paint machine over the pre-marked lines that have been prepared in the first step and spray or throw the paint onto the road. These tasks of the road painting that have been manually done in the above-mentioned system was accomplished in the autonomous robotics system using a small mobile robot prototype that was equipped with components of a painting system mounted on its platform. In this system, the autonomous navigation system is used to detect the exact position of the road that will be painted such as in the middle, at right or left. Based on the types of the road lane marks, the painting system is able to control the time periods for spraying the paint on the road. The control of the spray time is done using the main controller as a sharing component for the navigation with the painting systems. Experimental results for both road navigation and painting show the capability of the proposed algorithms to robustly drive the robot in given the road environments. The benefit of autonomous robotics system in comparison with manual two-machines system are to minimize blocking of the roads during painting and repainting of the faded marks; to shorten the time needed to perform the painting and to ensure high accuracy and reliability, since the process is performed autonomously with minimal human intervention.